Obinutuzumab in systemic lupus erythematosus: a real-world experience - Wu, Chunmei; Wang, Yinglu; Chen, Shenshen; Lin, Yanwei; Du, Fang; Wang, Xiaodong; Chen, Sheng; Lu, Liangjing; Ye, Shuang; Ding, Huihua; Fu, Qiong (Frontiers in Immunology, 2025)
ObjectivesTo describe the real-world efficacy and safety of obinutuzumab in a heterogeneous systemic lupus erythematosus (SLE) population, including severe or refractory manifestations.MethodsWe retrospectively analyzed 56 SLE patients who received a single dose of obinutuzumab (1000 mg) at Renji Hospital, Shanghai Jiao Tong University School of Medicine between October 2021 and March 2024. Patients were followed for 48 weeks. Outcomes included the proportion of patients achieving definitions of remission in systemic lupus erythematosus (DORIS), Lupus Low Disease Activity State (LLDAS), clinical stable, and flare. Changes in SLEDAI-2K, anti-dsDNA, complement levels, B cell counts, glucocorticoid dose, and adverse events were assessed. Subgroup analyses were performed to address population heterogeneity.ResultsAt baseline, 35.7% of patients were newly diagnosed, 57.1% had relapsing/refractory disease, and 7.1% were on maintenance therapy. By week 48, 37.5% achieved DORIS remission, 32.1% LLDAS, and 19.6% remained clinically stable. Mean SLEDAI-2K decreased from 11.75 ± 9.31 (range: 0 to 46) to 1.45± 1.93 (range: 0 to 8). Among 15 lupus nephritis patients, 86.7% achieved complete renal response. Significant hematologic improvement was observed in autoimmune hemolytic anemia and thrombocytopenia. B cell counts declined rapidly and began to repopulate from week 36. Glucocorticoids tapered from 43.04 ± 18.19 (range: 0 to 60) to 8.95 ± 9.78 (range: 0 to 50) mg/day. Obinutuzumab was well tolerated, with infections observed in 14 cases (25.0%) and infusion reactions in 4 cases (7.1%).ConclusionObinutuzumab showed favorable efficacy and safety in SLE, including severe/refractory manifestations, suggesting potential benefits for difficult-to-treat patients.